Design Of Speed, Agility, Quickness Exercises To Improve The Physical Fitness Of Students At The Muhammadiyah University Of Surakarta In Terms Of Speed and Endurance - Nur Subekti; Agam Akhmad Syaukani; Anugrah Nur Warthadi; Amar Abdullah Dani Arni Raihan; Raihan Budianto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the design of speed, agility, quickness exercises to improve the physical fitness of students at the Muhammadiyah University of Surakarta. The sample of this study was male students at the Sport Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta, with some 40 people, purposive sampling was used to determine the sample. This research method uses quasi-experimental research. Data analysis techniques use the constellation one group pretest_posttest design. Data analysis techniques use descriptive analysis and inferential analysis, descriptive analysis is used to describe the results of this study while inferential analysis uses paired sample tests at a significant level ? =0.05 analysis used with the help of SPSS version 20.0. The results of this study can be concluded.    Speed, Agility and Quickness  (SAQ) training models namely:(1)"A" Mark Walk, (2) 20-Yard Shuttle, (3) MB Wall Chest Passes,   (4) Vertical Jump, (5) Skip For Distance, (6) partner-Resisted Stars, (7) MB Over Head Throw, (8) Standing long Jump, (9) Skip For Height, (10) T-Drill, (11) Bullet Belt, (12) Squrium, (13) Hexagon Drill, (14) Quik Feet,  (15) X-pattern Multiskill, (16) Hop-Scotch Drill, (17) Z-pattern Ceuts, (18)One-Leg Hop, with a new concept designed according to the needs of Speed, Agility and Quickness (SAQ) training. The SAQ exercise design consisted of (1) cardiorespiratory endurance training; (2) muscle strength and endurance for the upper body, abdomen and lower body; (3) flexibility exercises both dynamic and static; (4) cardiorespiratory endurance activity; (5) endurance and muscle strength activities and (6) forms of flexibility activity.